The psychology of abnormality - Peterson, Christopher (Harcourt Brace College Publishers, 1996)
[The book] is a comprehensive yet efficient textbook on psychological disorders. Containing only 15 chapters, it is designed to fit readily within a typical academic term. Theoretically balanced, it includes DSM-IV criteria and up-to-date coverage; it places psychopathology in its multiple contexts (historical, social and cultural); it stresses the continuity between normality and abnormality; and it attends to human diversity more than the typical textbook.... Abnormal psychology is an extremely popular course at most colleges and universities. -Pref.